Roosting records in tree cavities by a forest-dwelling bat species (Histiotus magellanicus) in Andean temperate ecosystems of southern Chile - Altamirano, Tomás A; Ibarra, José Tomás; Novoa, Fernando; Vermehren, Alejandra; Martin, Kathy; Bonacic, Cristián (BOSQUE, 2017)
Tree cavities can provide critical roosting sites for cavity-using vertebrates. These sites can directly affect productivity and survival of bats. Histiotus magellanicus, one of the bat species with the southernmost distribution in the world, is suspected to use tree cavities, under bark, caves and human buildings for roosting. We document the first records of this bat roosting in tree cavities created by both cavity-facilitators (i.e., excavators) and tree-decay processes on standing dead and large decaying trees in Andean temperate forests, southern Chile. Our records contribute to improve current knowledge of roosting habitat of H. magellanicus. We discuss these natural history records on roosting site selection and the potential importance of tree cavities for this species in southern temperate ecosystems.